2001
DOI: 10.1093/bioinformatics/17.3.280
|View full text |Cite
|
Sign up to set email alerts
|

Genview and Gencode : a pair of programs to test theories of genetic code evolution

Abstract: GENVIEW: and GENCODE: are tools for testing the adaptive nature of a genetic code under different assumptions about patterns of genetic error and the nature of amino acid similarity. GENVIEW: provides a user friendly, point-and-click interface by which a user may reproduce and extend analysis of the adaptive properties of the standard genetic code or any of its secondary derivatives. GENVIEW: is a graphical user interface (GUI) program which runs on Linux, Unix and Microsoft Windows platforms and is based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…When they used weightings to allow for biases in translation, they found that only 1 in every million randomly generated codes was more efficient than the standard genetic code. In (Ronneberg et al, 2001) the authors presented a graphical tool for testing the adaptive nature of the genetic code under those assumptions about patterns of genetic error and the nature of amino acid similarity. Additionally, as the adaptability of the genetic code does not hold for other amino acid properties other than polar requirement, in (Freeland et al, 2000b) the authors applied point accepted mutation (PAM) 74-100 matrix data, which derives from frequently observed substitution patterns of amino acids in naturally occurring pairs of homologous proteins.…”
Section: Previous Workmentioning
confidence: 99%
“…When they used weightings to allow for biases in translation, they found that only 1 in every million randomly generated codes was more efficient than the standard genetic code. In (Ronneberg et al, 2001) the authors presented a graphical tool for testing the adaptive nature of the genetic code under those assumptions about patterns of genetic error and the nature of amino acid similarity. Additionally, as the adaptability of the genetic code does not hold for other amino acid properties other than polar requirement, in (Freeland et al, 2000b) the authors applied point accepted mutation (PAM) 74-100 matrix data, which derives from frequently observed substitution patterns of amino acids in naturally occurring pairs of homologous proteins.…”
Section: Previous Workmentioning
confidence: 99%
“…The standard genetic code table is published in a multitude of scientific papers and books. Numerous papers have been published in an attempt to explain the origin of the genetic code (Barbieri, 2003;Beebe et al, 2003b;Crick, 1968;Di Giulio, 1997, 1999a,b, 2000, 2001a,b, 2002Di Giulio and Medugno, 1998, 1999, 2001Freeland et al, 2003;Guimaraes, 2004;Jukes, 1993;Jukes and Osawa, 1993;Knight et al, 1999;Osawa et al, 1992;Ribas de Pouplana et al, 1998;Schimmel, 2000, 2001c;Ronneberg et al, 2000Ronneberg et al, , 2001Schimmel and Ribas de Pouplana, 1999;Schimmel and Wang, 1999;Seligmann and Amzallag, 2002;shCherbak, 2003;Skouloubris et al, 2003;Stevenson, 2002;Trevors, 2003;Wang and Schultz, 2002;Woese et al, 2000;Wong, 1975Wong, , 1988Xue et al, 2003;Yarian et al, 2002;Yarus and Christian, 1989;Yarus, 2000). All code origin models have problems and lack detail.…”
Section: The Role Of Natural Selectionmentioning
confidence: 99%